Break Even Point Analysis of Goderukem Production from Pine Mercusii Jungh et de Vriese - Fikri Muhaimin Firdaus; Sri Mutiar; Dewi Arziyah (Agricultural Revolution Journal, 2025)
The type and composition of sap varies for each type of pine. Break Even Point is where the total revenue point is equal to the total cost or the point that shows the total contribution margin is equal to the total fixed cost. This study aims to analyze the Break Even Point to find the point where production costs are equal to revenue. The product to be calculated is a processed product gondorukem (Resina colophonium) from pine resin which can be used as raw material for batik, leather, soap, paint, insulators, paper and varnish industries. This research is a descriptive study using quantitative methods, where the author will collect data in the form of numbers needed in connection with the problem to be examined, so that the results of his research can be more trusted and reliable truth. In addition, this research also uses literature studies to obtain the necessary theories, data and images. Based on the calculation of the Break Even Point value in units is 7,065 units of gondorukem products Rp.50,000, - / unit with Fixed Cost (FC) Rp.24,497,000, - annually and sales must reach Rp. Rp.349,957,143, - so it can be concluded that this product is feasible to produce.